Weedy Rice From South Korea Arose From Two Distinct De-domestication Events - Vigueira, Patrick A.; Olsen, Kenneth M.; Wagner, Christopher R.; Chittick, Zoey B.; Vigueira, Cynthia C. (Frontiers in Agronomy, 2020)
Agro-ecosystems are dominated by crop plants and the weedy species that thrive under agricultural conditions. Weedy crop relatives are some of the most difficult weeds to manage and can dramatically reduce crop yields when left unchecked. Weedy rice has resulted from multiple de-domestication events from crop rice in different rice growing regions. Interestingly, both South Korea and the United States harbor weedy rice populations that share ancestry with indica cultivars and temperate japonica cultivars. Here we compare weedy rice populations from South Korea and the United States on order to identify if they are the result of the same de-domestication events. We find that weedy rice populations in South Korea are genetically distinct from weedy rice found in the USA and are therefore the result of two unique de-domestication events. Low levels of genetic diversity among Korean weedy rice accessions (haplotype diversity = 0.0188 and 0.0324) indicate recent de-domestication events from crop relatives.